KAJIAN PENGGUNAAN PGPR (Plant Growth Promoting Rhizobacteria) TERHADAP VIABILITAS DAN VIGOR BENIH TOMAT (Solanum lycopersicum L.) - Nanda Fadila; Rita Hayati; Almuna Ramadhani (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2026)
This study aimed to evaluate the effect of Plant Growth Promoting Rhizobacteria (PGPR) on the viability and vigor of tomato seeds (Solanum lycopersicum L.). The research was motivated by the importance of high-quality seeds as the foundation of tomato cultivation. Seed viability and vigor determine uniformity, growth rate, and seedling tolerance under changing environmental conditions. The experiment was conducted at the Seed Science and Technology Laboratory, Faculty of Agriculture, Syiah Kuala University, using two tomato varieties (Karina and Grand Sakina F1) and eight rhizobacterial isolates (Azotobacter sp., Necercia sp., Pseudomonas capacia, Bacillus megaterium,Pseudomonas diminuta, Flavobacterium sp., Bacillus polymixa, and Bacillus stearothermophillus). A factorial completely randomized design (2×9) with three replications was applied. Results indicated that the Karina variety exhibited higher seed viability and vigor compared to Grand Sakina F1. PGPR treatments did not significantly affect viability; however, some isolates such as Necercia sp. and Bacillus stearothermophillus tended to improve vigor, particularly in vigor index, uniformity, and relative growth rate. Conversely, Flavobacterium sp. showed relatively lower vigor values. These findings highlight the importance of selecting superior varieties and suitable PGPR isolates to enhance the physiological quality of tomato seeds in a sustainable manner.